Relevansi Hadis Larangan Marah dengan Kesehatan Mental - Hammydiati Azifa Lazuardini I (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
This paper aims to find out the meaning contained in the Angry Hadith which is examined from the psychological aspect. This is based on a phenomenon that occurs where humans are often excessive in anger when facing one thing. Even though the Prophet SAW had said and called on his people not to be angry or emotional. Because angry behavior is not just the teachings conveyed, but the impact of anger will be very detrimental and affect the mental, psychological and neurological conditions. The research is qualitative research with analytical literature study method. The relevance of the hadith prohibits anger with mental health, which is seen from its neuropsychological effects, namely tense the nerves of the body, turbulence of blood and the tendency of an unstable brain. In addition, angry behavior is not only in the form of increasing psychological tension but also the emergence of negative behavior. Then anger can be minimized not only through psychological therapy but also spiritually. From the intervention in this study in the aspect of Islam, that this hadith can be used as a therapy or balancer in daily life, especially in anger, which can then be conveyed through da'wah pulpits, especially this hadith is included in the hadith so that it can become the basis law (hadith reference). So that from this reference, it is expected that humans can be better able to maintain behavior in their lives, be able to filter things well and no longer be easily provoked by emotions.